2010
DOI: 10.1098/rstb.2010.0067
|View full text |Cite
|
Sign up to set email alerts
|

In search of the last common ancestor: new findings on wild chimpanzees

Abstract: Modelling the behaviour of extinct hominins is essential in order to devise useful hypotheses of our species' evolutionary origins for testing in the palaeontological and archaeological records. One approach is to model the last common ancestor (LCA) of living apes and humans, based on current ethological and ecological knowledge of our closest living relations. Such referential modelling is based on rigorous, ongoing field studies of the chimpanzee (Pan troglodytes) and the bonobo (Pan paniscus). This paper r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 75 publications
0
61
0
Order By: Relevance
“…For example, several studies reported the use of hammers and anvils in order to crack nuts in capuchin monkeys [55,56] and chimpanzees [57,58]. These activities may require complex behavioural patterns, such as the selection of an efficient hammer, its transportation to the location of the anvil, and the choice of the most appropriate motor pattern (trajectory, force, etc.).…”
Section: Conclusion and Evolutionary Remarksmentioning
confidence: 99%
“…For example, several studies reported the use of hammers and anvils in order to crack nuts in capuchin monkeys [55,56] and chimpanzees [57,58]. These activities may require complex behavioural patterns, such as the selection of an efficient hammer, its transportation to the location of the anvil, and the choice of the most appropriate motor pattern (trajectory, force, etc.).…”
Section: Conclusion and Evolutionary Remarksmentioning
confidence: 99%
“…Insight into language evolution can be gained from the communicative systems of nonhuman primates (Slocombe, Waller, & Liebal, 2011), especially those of chimpanzees, our closest living relative (McGrew, 2010). Although not a 'missing link,' chimpanzees display a number of features considered characteristic of early human populations, such as fission-fusion social organisation and life at the forestsavannah interface (van Lawick-Goodall, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13]). This paper explores whether this technology was used for plant processing by hunter-gatherer societies of the Southern Levant.…”
Section: Introductionmentioning
confidence: 99%